Helium Cryostat for Experimental Study of Natural Turbulent Convection - Urban, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
V disertační práci je popsán heliový kryostat s experimentální válcovou konvekční celou pro studium proudění při přirozené konvekci za velmi vysokých Rayleigho čísel Ra (až do řádu 10^15) a Nusseltových čísel Nu (až do řádu 10^4). Pracovní látkou je studené 4He, které umožňuje díky výhodným fyzikálním vlastnostem dosažení velmi vysokých hodnot čísel Ra. Návrh kryostatu je založen na koncepci lázňových NMR kryostatů s nízkým odparem kryokapalin. Ve středu kryostatu je umístěna konvekční cela o průměru 300 mm a výšce 300 mm. Celu tvoří horní a spodní dno a výměnná střední část. Tyto díly jsou spojeny rozebíratelnými přírubami těsněnými indiovým drátem. Výměnná část umožňuje snadnou modifikaci geometrie cely. Hlavní přednost kryostatu spočívá v minimálním vlivu konstrukce cely a použitých materiálů na studovanou konvekci. Cela kryostatu je navržena pro pracovní tlaky do 250 kPa.

The thesis focuses on the design of a helium cryostat with an experimental convection cell for the study of natural turbulent convection in the range of Rayleigh numbers Ra up to 1015 and Nusselt numbers Nu up to 104. Cryogenic 4He gas is used as a working fluid for experimental studies due to its advantageous properties that allow reaching very high Ra numbers. The cryostat design is based on the conception of low-loss NMR magnet cryostats. In the centre of the cryostat a cylindrical convection cell of 300 mm in diameter and 300 mm in height is placed. The cell is made of middle, top and bottom parts. These are jointed together by flanges sealed by indium wires. The middle part is exchangeable and allows the geometry of the cell to be modified. The cell is designed for measurements at pressures up to 250 kPa. The main advantage of this cryostat is the minimal influence of the cell design and materials on the studied convection.
Helium Cryostat for Experimental Study of Natural Turbulent Convection
Keywords: heliový kryostat; turbulentní proudění; přirozená konvekce; Rayleigh-Bénardova konvekce; přenos tepla; Rayleighovo číslo; helium cryostat; turbulent flow; natural convection; Rayleigh-Bénard convection; heat transfer; Rayleigh number